2011
DOI: 10.1007/s10840-011-9633-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of patients with left atrial thrombus undergoing anticoagulant therapy

Abstract: D-dimer levels below 0.5 μg/mL is not enough to rule out LA thrombus in AF patients with well-controlled anticoagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 12 publications
2
26
1
1
Order By: Relevance
“…Sugiura, et al reported that LAA flow velocity and d-dimer concentration predicted residual LA thrombus in patients undergoing antithrombotic therapy. 18) In their study, the predictive value of LVEF did not reach statistical significance (P = 0.087), probably because there were fewer patients (225) in their study than in our study (431). Nevertheless, Sugiura, et al suggested LVEF contributed to the formation of LA thrombus under antithrombotic therapy.…”
Section: Discussioncontrasting
confidence: 64%
“…Sugiura, et al reported that LAA flow velocity and d-dimer concentration predicted residual LA thrombus in patients undergoing antithrombotic therapy. 18) In their study, the predictive value of LVEF did not reach statistical significance (P = 0.087), probably because there were fewer patients (225) in their study than in our study (431). Nevertheless, Sugiura, et al suggested LVEF contributed to the formation of LA thrombus under antithrombotic therapy.…”
Section: Discussioncontrasting
confidence: 64%
“…6 AF is a known risk factor for atrial thrombosis, stroke, and peripheral embolism. 7,8 AF causes blood stagnancy in the RA. Most likely, cardiac device leads in the RA are a nidus on which this stagnant blood can form clot.…”
Section: Discussionmentioning
confidence: 99%
“…CHA 2 DS 2 -VASc was an independent risk factor of LATH in some researches [5][6][7], while losing predictive value in some other studies [8][9][10]. Hence, we performed this meta-analysis aiming to determine whether CHA 2 DS 2 -VASc score has the ability to predict the presence of LA thrombus in patients with atrial fibrillation (AF).…”
mentioning
confidence: 99%
“…Our search identified 6 reports [5][6][7][8][9][10] enrolling a total of 2594 patients with AF. The investigator, publication year, total number of patients, definition of left atrial thrombus, cohort study design, and risk estimate method are summarized in Table 1.…”
mentioning
confidence: 99%